Systematic Review and Meta-Analysis of Clinically Relevant Executive Functions Tests Performance after COVID-19 - Boris B. Velichkovsky; Anna Y. Razvaliaeva; Alena A. Khlebnikova; Piruza A. Manukyan; Vladimir N. Kasatkin; Artem V. Barmin (Behavioural Neurology, 2023)
It is widely known that COVID-19 has a number of prolonged effects on general health, wellbeing, and cognitive functioning. However, studies using differentiated performance measures of cognitive functions are still not widely spread making it hard to assess the exact functions that get impaired. Taking into account the similarities between post-COVID ‘brain fog’ and chemofog, we hypothesized that executive functions (EF) would be impaired. Literature search yielded six studies with 14 effect sizes of interest; pooled effect size was small to medium (d=−0.35). Combined with a narrative synthesis of six studies without a comparison group, these results show that EF get impaired after COVID-19; although, in most cases the impairment is transient and does not seem to be severe. These results specify the picture of ‘brain fog’ and may help to discover its mechanisms and ways of helping people with long COVID.